Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Dok & Perkapalan Kodja Bahari (Persero) Galangan Jakarta II - Nikmah, Miftakhun; Astutik, Endang Puji (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This study aims to determine the Influence of Work Environment and Work Motivation on Employee Performance at PT. Dok & Perkapalan Kodja Bahari (Persero) Galangan Jakarta II either partially or simultaneously. The method used in this study is a quantitative method with an associative approach. The sampling technique used is a probability sampling technique with a simple random sampling method. The data analysis method uses simple regression tests, multiple linear regression, correlation coefficient, determination coefficient, partial t test and simultaneous F test. The results of this study show that: The Work Environment has a significant effect on employee performance. This is evidenced by the value of the correlation coefficient of 0.717, the calculated t value of 5.164 > t table 1.999 and the significance level of 0.000 < 0.05. Work Motivation has a significant effect on employee performance. This is evidenced by the value of the correlation coefficient of 0.761, the calculated t value of 2.624 > t table of 1.999 and the significance level obtained of 0.000 < 0.05. Work environment and work motivation have a positive and significant effect on employee performance. This is evidenced by the result of the multiple linear regression equation Y = 21.838 + 0.232 + 0.256. F values count 74.299 > F tables 3.14 and significance levels 0.000 < 0.05. The value of the correlation coefficient is 0.706 or 70.6%. As well as the value of the determination coefficient of 0.719 or 71.9%.